(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Research has reported declines in physical activity (PA) and increases in screen time in children and adolescents worldwide during the COVID-19 pandemic. However, it is unclear how the pandemic has impacted Scotland. The Active Healthy Kids Scotland COVID-19 Report Card aimed to examine the impact of the COVID-19 pandemic on PA and health of Scottish children and adolescents, assess changes in socio-economic and gender inequalities, and evaluate relevant policy responses to COVID-19. Methods: An expert panel graded ten PA and health indicators – Sedentary Behaviour, Overall PA, Organised Sport and PA, Active Play, Active Transportation, Physical Fitness, Diet, Obesity, Family and Peer Influence, and Community and Environment – primarily utilising nationally representative data between 2020 and 2022 (post-COVID-19) with comparable data prior to 2020 (pre-COVID-19). Adopting the Active Healthy Kids Global Alliance methodology, grades were determined based on the percentage of children and adolescents meeting established benchmarks for each indicator. The Government and Policy indicator was graded based on a pragmatic adaptation of the Health-Enhancing Physical Activity Policy Audit Tool version 2. Results: The following post-COVID-19 grades were assigned with comparison to the pre-COVID-19 grades (pre/post): Organised Sport and PA (B–/B); Active Transportation (C–/C). The remaining indicators were graded as ‘INC’ (inconclusive). Changes in socio-economic and/or gender inequalities from pre- to post-COVID-19 were found for the following indicators: Sedentary Behaviour, Overall PA, Organised Sport and PA, Diet, Obesity, and Family and Peer Influence. Policy response to COVID-19 was graded as A– (PA) and B (Diet). Conclusion: Although grades for Organised Sport and PA and Active Transportation remained stable, there was limited public health data to comprehensively examine the impact of the COVID-19 pandemic in Scotland. For many indicators, there were no suitable pre-COVID-19 and/or post-COVID-19 data, due to pandemic-related disruptions in national monitoring and declines in surveillance before the pandemic. The findings do suggest that inequalities have persisted and/or worsened for some indicators. Notwithstanding, there was evidence of good policies on physical activity and diet put in place to mitigate the effects of COVID-19.